Pengaruh Potensi Diri, Perencanaan Karir, Biaya Pendidikan, Status Sosial Ekonomi Orang Tuadan Teman Sebaya Terhadap Minat Melanjutkan Pendidikan Ke Perguruan Tinggi Pada Siswa Di SMAN 2 Kota Solok - Putra, Robi Dwi; Jolianis, Jolianis; Amelia, Mona (Universitas PGRI Sumatera Barat, 2023)
ABSTRACTThis study aims to analyze 1) the influence of self-potential on interest in continuing education to college, (2) the influence of career planning on interest in continuing education to college, (3) the effect of education costs on interest in continuing education to college, (4) the influence of socioeconomic status of parents on interest in continuing education to college, (5) peer influence on interest in continuing education to college (6) The influence of self-potential, career planning, tuition fees, socioeconomic status, parents and peers together on interest in continuing education to college. This type of research is associative research. The research was conducted in an odd semester, namely in July 2023. The population of this study was class XII social studies students of SMA N 2 Solok which amounted to 175 students with a sample of 89 (stratified random sampling). Data collection techniques using questionnaire questionnaires. Data analysis using logistic regression analysis and t-test. The results showed that: (1) Self-potential has a significant effect on the interest in continuing education to higher education as evidenced by the regression coefficient value of 2.116 with a value of 0.017. (2) Career planning has a significant effect on interest in continuing education to higher education as evidenced by the regression coefficient value of 2.086 with a GIS value of 0.017. (3) Tuition fees have a significant effect on interest in continuing education to higher education as evidenced by the regression coefficient value of 2.695 with a GIS value of 0.005. (4) The social status of parents has a significant effect on the interest in continuing education to higher education as evidenced by the regression coefficient value of 2.142 with a GIS value of 0.025. (5) Peers have a significant effect on interest in continuing education to higher education as evidenced by the regression coefficient value of 2.214 with a GIS value of 0.013. (6) self-potential, career planning, socioeconomic status of parents and peers are proven to jointly affect the interest in continuing education to higher education at SMA N 2 Solok as evidenced by a GIS value of 0.000.Keywords: Interest in continuing to college, self-potential, career planning, education costs, social status of parents.